Competition and constraint: Economic globalization and human resource practices in 23 European countries. Issue 2 (8th February 2016) - Koster, Ferry; Wittek, Rafael
Abstract : Purpose: – The purpose of this paper is to investigate three distinct hypotheses about the relationship between human resource (HR) practices (discretion and skill enhancement) and the level of trade openness and foreign direct investments of countries. Design/methodology/approach: – The study applies multilevel analysis using data of 16, 701 employees living in 23 European countries. Findings: – Based on the multilevel analysis mixed support is found for the hypothesis stating that economic openness is curvilinearly related (an inverted U) to the use of HR practices. While this holds for discretion, it does not for skill enhancement. Originality/value: – While economic globalization is often mentioned as an important factor in understanding organizational relations, there have only been few international comparative studies explicitly linking measures of economic openness and HR practices. This study investigate whether economic globalization is important or not.